Mobile Learning - Uther, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Mobile learning has become one of the more influential aspects of the field of educational technology, given the ubiquity of modern mobile devices and proliferation of educational applications or 'apps'. Within this volume, there are a range of studies and reviews which cover a breadth of current topics in the field, namely user motivations for using mobile learning, issues in evaluation, as well as domain-specific considerations (e.g., use within language learning or audio-based applications). Together, these studies represent the synthesis of a range of methods, approaches, and applications that highlight benefits and areas of future growth of mobile technologies and how they can be useful and most effective in education.